Acute kidney injury as a prognostic factor in traumatic brain injury: rotterdam score association - Fa'izah, Chintya Nur; Husodo, Kharisma Ridho (Universitas 'Aisyiyah Yogyakarta, 2025)
Traumatic brain injury (TBI) is a major cause of disability and mortality worldwide, affecting nearly 50 million people annually. Acute kidney injury (AKI) is a potential complication in critically ill patients, but its relationship with TBI severity remains unclear. This study aimed to assess the association between AKI, Rotterdam score, length of stay (LOS), and outcomes in TBI patients. A cross-sectional study was conducted using medical records of TBI patients admitted to Yogyakarta Islamic Hospital PDHI from 2019 to 2022. Inclusion criteria were age 15–65 years, confirmed TBI diagnosis, head CT scan, and completed hospital treatment. Patients with pre-existing kidney disease, direct renal trauma, shock, or other AKI-related factors were excluded. Rotterdam scores were obtained from radiologist reports. Statistical tests assessed associations between AKI and clinical variables. Seventy-two patients met the criteria; 26.4% developed AKI. Higher Rotterdam scores (4–6) were significantly associated with AKI (p = 0.026). No significant association was observed between AKI and LOS (p = 0.393). AKI was strongly associated with poor outcomes (p = 0.004), with mortality rates of 26.3% in AKI patients compared to 1.9% in non-AKI patients. Higher Rotterdam scores may indicate increased AKI risk in TBI patients, and AKI is associated with markedly worse outcomes. Early recognition and management of kidney injury in high-risk patients may improve survival. Further prospective studies are needed to confirm these findings and explore preventive strategies.